Bukovina: Authors, Journals, Research Issues (Scientometric Analysis on WoS Basis) - Shyliuk, O. I. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Objective. The goal of research was to study publications containing researches and studies related to the topic of Bukovina using the bibliometric analysis. Methods. Materials on the regional topic published within the period 1970 – 2018 were obtained from the Web of Science database (as of May 15, 2019). The obtained records were analyzed for citation characteristic, including the distribution of publications over languages, countries, journals and authors. The selection by keywords: (bukovina) OR (bucovina) OR (bukowina) OR (bukovyna) identified 304 materials published in different publications. For the period from 2008 until 2019 there has been observed the significant increase of materials published on this issue. Results. The analysis of the most citable publications allows to distinguish three clusters of research topics: geology, environment and natural resources of the region; ethnic studies; the Holocaust and acts of force during the World War II. Conclusions. This study provides the systematic review of productivity and clearness of the Bukovina’s studies and can be used for organization and identification of priorities for further regional studies